Obrona decyzji sumienia przez Tomasza More’a w obliczu uwięzienia i śmierci - Medwid, Wojciech (Poznańskie Studia Teologiczne, 2016)
The article analyses Thomas More’s firm attitude defending his conscience, which did not allow him to swear an oath. The basis for reflection is his prison correspondence, especially with her daughter Margaret. He remained faithful to his conscience because he refused to submit the required signatures and was beheaded, but gained eternal salvation. He studied for a long time, meditated and prayed to make the right decision. The closest urged him to change his decision, but he refused. He was not affected by accusations, slander, threats or flattery. He did not swear an oath and did not explain anything. He preserved freedom of conscience and responsibility for his own decisions. He did not judge anyone else. All the time he showed respect and loyalty to the king and constantly assured of his prayers in king’s intentions. Despite the weakness and fear of death, he put everything into God's hands. He was a prisoner of conscience and gave his live in the name of fidelity to the Church and the Holy See.